Pension Management Challenges and Retirement Life Experiences: A Policy Implication - Adewumi, Samson (International Journal of Economics and Financial Issues, 2024)
Remarking on the discourse of pension management in Nigeria, scarce research attention can be traced to the understanding of pension management challenges and life after retirement experience through the prism of policy implication. To address this gap, the study assesses the pattern of pensioners’ life after retirement, the arrays of pension management challenges, and appropriate policy implications for effective pension management. A mixed-method research approach was employed. 345 retirees were randomly recruited and administered a questionnaire, and 18 purposively semi-structured interviews were conducted with the Federal Parastatals and Private Sector Pensioners Association of Nigeria. Quantitative data were analyzed with the frequency distribution and the Q-Q plot to determine the normal probability plot, while the NVivo (12) qualitative software was used for the identification of themes and sub-themes from the transcribed data. Findings revealed prolonged health challenges, poverty, and abrupt pension payment as life after retirement experiences. Verification bottleneck, poor monitoring and evaluation efforts, and administrative incompetency were issues around pension management challenges. The implication includes addressing political interference in pension management and administration, safeguarding retirees’ savings through legal commitment, and a call for employers’ contributions. The study recommends that the National Pension Commission become more responsive in its role of providing quality pension service, especially in terms of quality leadership, monitoring, and evaluation of Pension Fund Administrators.